Recherches sur les Mutillides de l’Afrique (Hymenoptera, Mutillidae) - XIX. Remarques concernant la Trogaspidia floralis (Klug, 1829) et formes ou espèces apparentées, déjà connues ou nouvelles (Deuxième contribution a la connaissance du genre Trogaspidia de l’ Afrique). - Nonveiller, Guido; Petersen, Børge (Contributions to Entomology = Beiträge zur Entomologie, 1995)
After a historical survey the status, synonymy and a detailed description of males and females of each of the following closely related species of the genus Trogaspidia is presented: floralis (Klug, 1829), bioculata (Sichel & Radoszkowsky, 1870), miniaticeps Bischoff, 1920 and major new species. They are distributed in the Afrotropical and partly in the Palaearctic region. Keywords Trogaspidia floralis, bioculata, miniaticeps Bisch., major spec. nov., Region afrotropicale, Yemen, Arabie Saoudite, Egypte, Libye, Algerie. Nomenclatural Acts major Nonveiller & Petersen, 1995 (Trogaspidia), spec. n.